2013
DOI: 10.1371/journal.pone.0071914
|View full text |Cite
|
Sign up to set email alerts
|

Connected Text Reading and Differences in Text Reading Fluency in Adult Readers

Abstract: The process of connected text reading has received very little attention in contemporary cognitive psychology. This lack of attention is in parts due to a research tradition that emphasizes the role of basic lexical constituents, which can be studied in isolated words or sentences. However, this lack of attention is in parts also due to the lack of statistical analysis techniques, which accommodate interdependent time series. In this study, we investigate text reading performance with traditional and nonlinear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 56 publications
2
53
0
Order By: Relevance
“…• Wallot et al (2013), identified adult readers take an average of 5 minutes to read one page of information. However, based on the personal experience of the authors of this study, it has been determined that a total of 25 minutes is a more representative time in order to read and understand the information provided in 1 page.…”
Section: Specific Goals Of This Project Includedmentioning
confidence: 99%
See 2 more Smart Citations
“…• Wallot et al (2013), identified adult readers take an average of 5 minutes to read one page of information. However, based on the personal experience of the authors of this study, it has been determined that a total of 25 minutes is a more representative time in order to read and understand the information provided in 1 page.…”
Section: Specific Goals Of This Project Includedmentioning
confidence: 99%
“…Figure 10 presents the distribution of the air emissions being released the atmosphere most likely by the production process and user use. This phenomenon could be explained because computer production and use requires a great amount of energy [13].…”
Section: Impact Category Total Unitmentioning
confidence: 99%
See 1 more Smart Citation
“…As we scale up once more from sentence to connected text reading, lexical features loose their constitutive role for the reading process all together (Wallot, Hollis, & van Rooij, 2013). Similarly, text coherence metrics that were developed to characterize text reading fail to yield many of their predicted effects on a reader's performance, if one observes reading of long connected text that spans more than a few paragraphs (McNerney, Goodwin, & Radvansky, 2011).…”
Section: Reading Is Complex Not Just Complicatedmentioning
confidence: 99%
“…This is due to the dynamic nature of the reading process, which exhibits quite complex dynamics: For example, reading of connected text leads to highly nonstationary reading times (Wallot, Hollis, & van Rooij, 2013), where a single word can have a significant impact on how reading performance changes over the next several hundred words (Booth, Brown, Eason, Wallot, & Kelty-Stephen, 2016) and where qualitative changes in reading performance occur (Wallot, O'Brien, Haussmann, Kloos, & Lyby, 2014), which are potentially indicative of qualitative shifts in the mental representations as a function of comprehension (Stephen, Dixon, & Isenhower, 2009). Moreover, the problem with naturalistic texts is that they are highly structured stimuli that cannot be experimentally manipulated, as one can do with random word lists in lexical decision and naming tasks, because the different psychologically relevant text descriptors are highly correlated among each other (Graf, Nagler, & Jacobs, 2005) and with the syntactical structure of a text (e.g., Keller, Carpenter, & Just, 2001) and their effects change across the time-course of reading (McNerney, Goodwin, & Radvansky, 2011;Teng, Wallot, & Kelty-Stephen, 2016;.…”
Section: Introductionmentioning
confidence: 99%